2001
DOI: 10.1902/jop.2001.72.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and Lymphocyte Subpopulations in Nifedipine‐ and Cyclosporin A‐Associated Human Gingival Overgrowth

Abstract: The results support the idea that immune response may be altered in drug-induced gingival overgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
(31 reference statements)
3
25
0
Order By: Relevance
“…Many studies have shown that drugs with immunomodulating effects always cause changes of lymphocyte subpopulations (15), which thus lead us to investigate the effects of SPMG on the T lymphocyte subset in peripheral blood mononuclear cells (PBMC) (Fig. 3).…”
Section: Spmg Enhanced the Ratio Of Cd4 Over Cd8 In T Lymphocytesmentioning
confidence: 99%
“…Many studies have shown that drugs with immunomodulating effects always cause changes of lymphocyte subpopulations (15), which thus lead us to investigate the effects of SPMG on the T lymphocyte subset in peripheral blood mononuclear cells (PBMC) (Fig. 3).…”
Section: Spmg Enhanced the Ratio Of Cd4 Over Cd8 In T Lymphocytesmentioning
confidence: 99%
“…3b). j-AAV-CsA animals showed persistent CD68 staining independently of circulating ARSB levels (data not shown), probably due to CsA side effects (Pernu and Knuuttila, 2001;Ghee et al, 2008). Importantly, in AF animals receiving CTLA4-Ig alone, either at birth or on P30 (AF þ CTLA4-Ig), tissue GAG accumulation (GAG levels: in the liver, 7.9 AE 0.3; in the kidney, 11.7 AE 0.7; in the spleen, 11.4 AE 0.3) and macrophage infiltration were similar to those observed in AF animals (Fig.…”
mentioning
confidence: 90%
“…[4][5][6] It has been previously reported that CsA and nifedipine medication affect numbers of Langerhans cells 7 and macrophages 8,9 in overgrown gingiva and may play roles in qualitative changes in inflammatory response. Dihydropyridines are calcium-channel blocking agents often taken by patients with cardiovascular disorders and undergoing organ transplantation.…”
mentioning
confidence: 99%